2008
DOI: 10.1111/j.1365-2249.2008.03811.x
|View full text |Cite
|
Sign up to set email alerts
|

Human bronchial intraepithelial T cells produce interferon-γ and stimulate epithelial cells

Abstract: SummaryIntraepithelial lymphocytes (IELs) can be identified among epithelial cells in systemic mucosal tissues. Although intestinal IELs play a crucial role in mucosal immunity, their bronchial counterparts have not been well studied. The purpose of this study was to determine the immunological functions of human bronchial IELs, which interact directly with epithelial cells, unlike lamina propria lymphocytes (LPLs). We isolated successfully bronchial IELs and LPLs using a magnetic cell separation system from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…However, our findings in this group are comparable to data published by Hirosako et al, who have meticulously analyzed CD103 + expression by intraepithelial T cells in human bronchi (third to fifth generation) in a patient group that is demographically very similar to our cohort (14,16). They showed that a range of 74% to 94% of intraepithelial CD8 + cells expressed CD103, whereas only 8% to 25% of lamina propria T cells expressed CD103.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, our findings in this group are comparable to data published by Hirosako et al, who have meticulously analyzed CD103 + expression by intraepithelial T cells in human bronchi (third to fifth generation) in a patient group that is demographically very similar to our cohort (14,16). They showed that a range of 74% to 94% of intraepithelial CD8 + cells expressed CD103, whereas only 8% to 25% of lamina propria T cells expressed CD103.…”
Section: Discussionsupporting
confidence: 91%
“…Immunohistochemistry confirmed that most lung CD103 + CD3 + CD8 + T cells were indeed located intraepithelially above the basement membrane of the small airways ( Figure 1C), as was previously published (13)(14)(15)(16).…”
Section: Human Lung Cd8 + T Cells Expressing αE Integrin Are Ielssupporting
confidence: 86%
See 1 more Smart Citation
“…Subsequently, we isolated bronchial IELs and LPLs from resected lung tissue and showed that IELs produced γ-interferon, which stimulated bronchial epithelial cells, and that IELs could be maintained by epithelial cells [12]. However, to date, a comparative evaluation of phenotypes of both bronchial IELs and LPLs in both normal and pathological states has not been made.…”
Section: Introductionmentioning
confidence: 99%
“…However, such processes can alter the expression of some cellular surface markers [14]. Furthermore, isolation of bronchial IELs using conventional separation methods is challenging and requires short-time incubation of bronchial specimens with interleukin (IL) 2 [12] due to smaller sample size and complex branching structure of the tissue. Such treatment may further alter the cells’ surface antigen profile.…”
Section: Introductionmentioning
confidence: 99%